Total body water and failure to control blood pressure by medication in hemodialysis patients - Santi Xavier, Patrícia [UNESP]; Vogt, Bárbara Perez [UNESP]; Cuadrado Martin, Luis [UNESP]; Vaninni, Francieli [UNESP]; Antunes, Aline Araújo [UNESP]; Ponce, Daniela [UNESP]; Caramori, Jacqueline Costa Teixeira [UNESP]; Martin, Rosana dos Santos e Silva [UNESP]; Franco, Roberto Jorge da Silva [UNESP]; Barretti, Pasqual [UNESP] (Karger Publishers, 2014)
Background: Volume overload is the main factor responsible for the pathogenesis of hypertension in dialysis patients. Few studies have evaluated the interpretation of the parameters obtained by bioelectrical impedance (BIA) to manage these patients. The aim of this study was to assess the best cutoff level of volume overload obtained by BIA able to predict the absence of hypertension control in hemodialysis patients. Methods: Volume overload was calculated as the difference between total body water (TBW) measured by bioimpedance and TBW estimated by the Watson formula in chronic stable hemodialysis patients. Inadequate control of blood pressure (BP) was defined as the mean of measurements obtained before five hemodialysis sessions ≥140 × 90 mm Hg. The best cutoff level of volume overload assessed by BIA able to predict the absence of BP control in patients on chronic hemodialysis was determined by the receiver operating characteristic (ROC) curve using the Youden method. Results: We included 205 patients, 53% male, aged 56 ± 14.5 years. The largest area under the ROC curve was found for predialysis volume overload (0.660, 95% CI 0.556–0.765, p = 0.004). The ROC curve of postdialysis volume overload also reaches statistical significance. The best cutoff point was found for predialysis volume overload ≥1.4 liters with a sensitivity of 69% and a specificity of 67%. Conclusion: The association of TBW and inadequate BP control highlights the importance of volume management in hemodialysis patients. Predialysis volume overload of 1.4 liters was the parameter that best discriminated the presence of inadequate BP control.
Keywords: Extracellular volume; Bioimpedance analysis; Blood pressure; Hemodialysis